Reconciling pre-Columbian settlement hypotheses requires integrative, multidisciplinary, and model-bound approaches - Bortolini, Maria Catira (2014)
Achilli et al. (1) present unique evidence concerning human mitogenomes and argue that such data are sufficient to generate a consensus scenario for the first settlement of the Americas. Here, we challenge their statement of having achieved a reconciling model because it ignores coherent ideas recently proposed by many researchers.